Solid ground 25 years of evangelical theology - Trueman, Carl R.; Gray, Tony J.; Blomberg, Craig L. (Leicester, UK IVP, 2000)
Includes bibliographical references.
Celebrating the 25th anniversary of the journal, Themelios.
Keywords: Evangelicalism -- theology